Quality of Residual Neuromuscular Control and Functional Deficits in Patients with Spinal Cord Injury - Ovechkin, Alexander; Vitaz, Todd; Terson de Paleville, Daniela; McKay, William B. (Frontiers in Neurology, 2013)
Study Design: Prospective cohort study Objective: This study examined the relationship between motor control and clinical function outcomes after spinal cord injury (SCI). Setting: University of Louisville, Louisville, Kentucky, USA. Material: Eleven persons with SCI and 5 non-injured subjects were included in this study. Methods: The American Spinal Injury Association Impairment Scale (AIS) was used to categorize injury level and severity. Multi-muscle, surface EMG (sEMG) recording, was carried out using a protocol of reflex and volitional motor tasks and was analyzed using a vector-based tool that calculates index values that relate a distribution of multi-muscle activation pattern of each SCI subject to the prototype obtained from non-injured subject group and presents overall magnitude as a separate value. Functional Independence Measure (FIM) motor subscale, Spinal Cord Injury Independence Measure (SCIM-III), and Walking Index for Spinal Cord Injury (WISCI) scale scores were compared to neurophysiological parameters. Results: AIS category and injury level correlated significantly with the WISCI and SCIM mobility subscales. sEMG-derived parameters were significantly correlated with SCIM and WISCI scores but only for examinations carried out 48 or more days post-injury. Conclusions: These results supported the hypothesis that clinically-relevant function after SCI is related to the degree to which functional organization within the central nervous system is disrupted. Further, due likely to the constraints placed on the expression of functional ability by early post-injury immobilization and hospitalization, neurophysiological assessment of motor function may provide better sensitivity and reliability than can be obtained using the clinical function scales examined here within the early period after injury.